PROFESSIONAL ORIENTATION OF MATHEMATICAL TRAINING OF THE BACHELOR IN NAVIGATION - Cherkas, Olena; Bykovets, Natalia; Chumachenko, Mariya (Professional Pedagogics, 2019)
The article discusses the competences in Mathematics of a prospective Bachelor in Navigation. Mathematical competence is defined as a function of competencies: general and subject-specific. It’s manifested that mathematics acts as a fundamental discipline for the further mastering of specialized disciplines. The article suggests the competence approach to mathematical education based on the analysis of professional requirements as the methodology of the research. The article states the principal provisions of the competence approach in terms of the Tuning methodology; classification of the general and subject-specific competencies of the Bachelor in navigation required for successful professional activities; analysis of the structure and content of the mathematical training of the prospective Bachelor in Navigation in some Higher Maritime Educational Institutions in Ukraine and Europe. In accordance with the IMO (International Maritime Organization, 2014) standards, the requirements for teaching mathematics to the undergraduate students are presented. The analysis of the determined tasks as well as cooperation with the lecturers of the specialized disciplines allows to formulate the content of the Higher Mathematics course paying sufficient attention to those sections of mathematics that are necessary for vocational training of the navigators; the contribution of the mathematical competence to the integral, general and special competencies indicated in the profile of a higher educational institution is manifested. The article suggests that the tools and approaches of the Tuning project provide effective monitoring, evaluation and improvement of the curriculum for achieving the object and making pertinent changes in the relevant subject areas.